Kepala Madrasah dan Kinerja Guru - Sufinatin Aisida (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
The head of the Madrasah is the manager of the institution which is one of the key in improving the teacher's performance, because Madrasah Tsanawiyah Al-Ihsan is one of the institutions under the auspices of the Ministry of Religious Affairs. This research is focused on the managerial competence of Madrasah head in improving teacher performance. This study uses ethnographic studies with a qualitative approach, which is done by MTs Al-Ihsan Krian. The findings of this research are as follows: (1) The planning undertaken by the head of MTs Al-Ihsan includes: (a) planning based on the vision, mission, objectives of the school, and need Assesment, (b) involving all elements of the school's Akademika (2) The implementation by the head of MTs Al-Ihsan Krian includes: (a) participating in training, seminars, and workshops, (b) forming a syllaaturant inter-Teacher Forum, (c) Improving teacher welfare, (d) Addition of supporting facilities, (e) Optimizing Counseling Guidance, (f) Finger print teacher certification. (g) Reward and Punishment (3) evaluation conducted by the head of MTs al-Ihsan Krian includes: (a) conducting supervision, both personally and in groups, (b) the techniques used are directly (Directive) and indirect (non direcvtive), (c) The evaluation aspect in supervision is the teacher's presence, teacher's performance in school, student development, RPP, and syllabus.